China's Local Entrepreneurial State and New Urban Spaces Downtown Redevelopment in Ningbo - Zhang, Han.; SpringerLink (Online service) (New York : Palgrave Macmillan US (Imprint), 2016)
In this book, the author seeks to understand China's urban redevelopment from the theoretical perspective of the local entrepreneurial state. China's rapid socio-economic transformations since 1978 have been in large part attributed to China's state transformations. The author closely investigates Ningbo's two downtown redevelopment projects by conducting ethnographic fieldwork and documentary research. It is found that the local entrepreneurial state deploys local state enterprises to undertake strategic urban redevelopment projects, organizes high-profile city/district marketing campaigns in entrepreneurial manners, and develops corporatist intermediations with local business owners for collaborative urban governance. Yet the local entrepreneurial state is multi-layered, with the municipal and district authorities sometimes disagreeing, conflicting, and bargaining with each other. Meanwhile, the relationship between spaces and their users, as well as that between various space users, constantly changes. All these players and their interactions constitute "spatial politics", or the story of conflicts, struggles, negotiations, and collaborations in urban governance. This work, based on six months of fieldwork, will appeal to scholars in the social sciences and experts in Asian Studies.
1. Introduction -- 2. The "City Operator" and the Tianyi Square Redevelopment Project -- 3. Ningbo's Historic Laowaitan -- 4. The Redevelopment of the Laowaitan -- 5. The New Urban Spaces of the Laowaitan -- 6. The Flawed Governance of the Laowaitan and the Coping Strategies -- 7. Conclusion and Discussion.
Keywords: Sociology, Urban; Ethnology-Asia.; Economic development; Human geography; Demography